The Biting Midge Culicoides sonorensis (Diptera: Ceratopogonidae) Is Capable of Developing Late Stage Infections of Leishmania enriettii - Seblova, Veronika; Sadlova, Jovana; Vojtkova, Barbora; Votypka, Jan; Carpenter, Simon; Bates, Paul Andrew; Volf, Petr (PLoS neglected tropical diseases, 2015)
BACKGROUND: Despite their importance in animal and human health, the epidemiology of species of the Leishmania enriettii complex remains poorly understood, including the identity of their biological vectors. Biting midges of the genus Forcipomyia (Lasiohelea) have been implicated in the transmission of a member of the L. enriettii complex in Australia, but the far larger and more widespread genus Culicoides has not been investigated for the potential to include vectors to date. METHODOLOGY/PRINCIPAL FINDINGS: Females from colonies of the midges Culicoides nubeculosus Meigen and C. sonorensis Wirth & Jones and the sand fly Lutzomyia longipalpis Lutz & Nevia (Diptera: Psychodidae) were experimentally infected with two different species of Leishmania, originating from Australia (Leishmania sp. AM-2004) and Brazil (Leishmania enriettii). In addition, the infectivity of L. enriettii infections generated in guinea pigs and golden hamsters for Lu. longipalpis and C. sonorensis was tested by xenodiagnosis. Development of L. enriettii in Lu. longipalpis was relatively poor compared to other Leishmania species in this permissive vector. Culicoides nubeculosus was not susceptible to infection by parasites from the L. enriettii complex. In contrast, C. sonorensis developed late stage infections with colonization of the thoracic midgut and the stomodeal valve. In hamsters, experimental infection with L. enriettii led only to mild symptoms, while in guinea pigs L. enriettii grew aggressively, producing large, ulcerated, tumour-like lesions. A high proportion of C. sonorensis (up to 80%) feeding on the ears and nose of these guinea pigs became infected. CONCLUSIONS/SIGNIFICANCE: We demonstrate that L. enriettii can develop late stage infections in the biting midge Culicoides sonorensis. This midge was found to be susceptible to L. enriettii to a similar degree as Lutzomyia longipalpis, the vector of Leishmania infantum in South America. Our results support the hypothesis that some biting midges could be natural vectors of the L. enriettii complex because of their vector competence, although not Culicoides sonorensis itself, which is not sympatric, and midges should be assessed in the field while searching for vectors of related Leishmania species including L. martiniquensis and "L. siamensis".
Keywords: morčata; Animals; Leishmaniasis; Leishmania enriettii; křeček rodu Mesocricetus; Guinea Pigs; Mesocricetus; leishmanióza; Female; zvířata; hmyz - vektory; Gastrointestinal Tract; gastrointestinální trakt; Insect Vectors; ženské pohlaví; Psychodidae; Ceratopogonidae